Psychometrical analysis of Warr, Cook & Wall Job Satisfaction Scale in a multioccupational sample from Arequipa, Peru - Walter L. Arias; Renzo Rivera; Karla D. Ceballos (Interacciones)
The study, has as aim to make a psychometric analysis of the Overall Job Satisfaction Scale of Warr Cook and Wall (1979) in a sample of workers who are settled in Arequipa City (Peru). We tested 454 subjects with different Jobs by using the adapted version to Spanish by Pérez-Bilbao and Fidalgo (1995). We found that the scale has an unidimensional structure with good adjustment to the statistical criteria applied according to the confirmatory factor analysis. Moreover, the scale has a high reliability index (α= .945) and item-test correlations over .589.